High energy density solid-state supercapacitors based on porous carbon electrodes derived from pre-treated bio-waste precursor sugarcane bagasse. (1st November 2022) - Mohit; Yadav, Neetu; Hashmi, S.A.
Abstract: Supercapacitors with hierarchical porous carbon electrodes and ionic liquid incorporated quasi-solid-state gel polymer electrolyte are of the current area of interest as environment friendly and cost-effective power sources. Herein, we report hierarchical porous activated carbons (ACs) derived from a waste-bioresource sugarcane bagasse, prepared following hydrothermal and solvent (ethanol) soaking pre-treatments, followed by chemical/physical activations. AC-powders obtained from hydrothermal and ethanol-soaking pre-treatments show an increase in microporosity with optimum mesoporous interiors suitable to use as supercapacitor electrodes. The ACs have been electrochemically tested as supercapacitor electrodes with flexible quasi-solid-state gel polymer electrolyte comprising 0.5 M sodium triflate (NaTf) in an ionic liquid 1-ethyl-3-methylimidazolium trifluoromethane-sulfonate (EMITf) incorporated in poly(vinylidene fluoride-hexafluoropropylene) (PVdF-HFP) with high ionic conductivity ( 8.5 mS cm −1 ) and high electrochemical stability ( 4.7 V versus Ag/Ag + ). The supercapacitor based on AC-electrodes obtained after ethanol soaking pre-treatment i.e., ESB-electrodes show optimum charge-discharge performance in terms of specific capacitance ( 193 F g −1 ), specific energy ( 32 Wh kg −1 ) and maximum power density ( 55 kW kg −1 ). The ESB-based supercapacitors also illustrate relatively high rate-performance as compared to other AC-electrodes, studied in this report. The high energy storage in the supercapacitor is evident from the glow of LED for substantial duration. The device shows stability up to 10, 000 charge-discharge cycles with 20 % initial fading in specific capacitance and 100 % Coulombic efficiency. Graphical abstract: Unlabelled Image Highlights: Activated carbons (ACs) from sugarcane bagasse (SB) found suitable EDLC-electrodes. Ethanol-soaking treatment substantially improves electrochemical behaviour of AC. Solid-state EDLC with flexible gel electrolyte shows high capacitance ( 193 F g −1 ). Device stores high energy ( 32 Wh kg −1 ) with maximum power ( 55 kW kg −1 ). The EDLC shows stable performance for 10, 000 GCD cycles with 20 % initial fading.